Transcriptional induction of prostaglandin G/H synthase-2 by basic fibroblast growth factor. - H Kawaguchi; C C Pilbeam; G Gronowicz; C Abreu; B S Fletcher; H R Herschman; L G Raisz; M M Hurley (The Journal of Clinical Investigation, 1995)
In serum-free mouse osteoblastic MC3T3-E1 cells, basic fibroblastic growth factor (bFGF) induced mRNA and protein for prostaglandin G/H synthase-2 (PGHS-2), the major enzyme in arachidonic acid (AA) conversion to prostaglandins. mRNA accumulation peaked at 1 h with bFGF 1 nM. In cells stably transfected with a 371-bp PGHS-2 promoter-luciferase reporter, bFGF stimulated luciferase activity, which peaked at 2-3 h with bFGF 1-10 nM. In the presence of exogenous AA, bFGF stimulated PGE2 production, which paralleled luciferase activity. In serum-free neonatal mouse calvarial cultures, bFGF stimulated PGE2 production in the absence of exogenous AA. bFGF stimulated PGHS-2 mRNA accumulation, which peaked at 2-4 h and then decreased; there were later mRNA elevations at 48 and 96 h that were inhibited by indomethacin. In both MC3T3-E1 cells and neonatal calvariae, bFGF produced smaller and slower increases in PGHS-1 mRNA levels than for PGHS-2. bFGF stimulated bone resorption in mouse calvariae with a maximal increase of 80% at 1 nM. Stimulation was partially inhibited by nonsteroidal anti-inflammatory drugs. We conclude that bFGF rapidly stimulates PGE2 production in osteoblasts, largely through transcriptional regulation of PGHS-2, and that prostaglandins mediate some of bFGF's effects on bone resorption. Images